European Green Mutual Fund Performance: A Comparative Analysis with their Conventional and Black Peers - Ibikunle, Gbenga (Journal of business ethics, 2017)
We conduct the first comparative analysis of the financial performance of European green, black (fossil energy and natural resource) and conventional mutual funds. Based on a unique dataset of 175 green, 259 black and 976 conventional mutual funds, the investigation contrasts the financial performance of the three dissimilar investment orientations over the 1991–2014 period. Over the full sample period, green mutual funds significantly underperform relative to conventional funds, while no significant risk-adjusted performance differences between green and black mutual funds could be established during the same period. Environmentally friendly investment vehicles display a significant exposure to small cap and growth stocks, while black funds are more exposed to value stocks. Remarkably, the green funds’ risk-adjusted return profile progressively improves over time until no difference in the performance of the green and the conventional classes could be discerned. Further evidence suggests that the green funds are beginning to significantly outperform their black peers, especially over the 2012–2014 investment window.